2004
DOI: 10.1109/tps.2004.826041
|View full text |Cite
|
Sign up to set email alerts
|

Operational Characteristics of a Periodic Plasma Torch

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense. Washington Headquarters Sereices, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A reduction in the ignition delay time would lead to an increase in the performance and efficiency of the engine. Modeling the conditions and evolution of such engines when a plasma is introduced, through a plasma torch, has shown that the reaction efficiencies increase and the ignition delay time decreases (Masuya et al, 1993;Williams et al, 2000;Kuo et al, 2004;Kahandawala et al, 2006). This effect could be due to many factors such as the increased temperature or decomposition of the larger fuel molecules to smaller fragments with a lower ignition threshold.…”
Section: Hydrocarbon Chemistrymentioning
confidence: 99%
“…A reduction in the ignition delay time would lead to an increase in the performance and efficiency of the engine. Modeling the conditions and evolution of such engines when a plasma is introduced, through a plasma torch, has shown that the reaction efficiencies increase and the ignition delay time decreases (Masuya et al, 1993;Williams et al, 2000;Kuo et al, 2004;Kahandawala et al, 2006). This effect could be due to many factors such as the increased temperature or decomposition of the larger fuel molecules to smaller fragments with a lower ignition threshold.…”
Section: Hydrocarbon Chemistrymentioning
confidence: 99%
“…Oxidization of B. cereus bacterial spores by reactive radicals generated in the plasma effluent (such as O, NO and O 3 ) or in water (such as OH•) is then considered to be the mechanism of killing spores in the experiments. Chemically reactive oxygen species (ROS) [ 4 , 34 - 36 , 39 ] are known to be effective in the destruction and annihilation of bacterial spores, and atomic oxygen is probably the most effective one among them in decontamination.…”
Section: Plausible Mechanismmentioning
confidence: 99%
“…Therefore, the 4 cm exposure distance is reachable only by some of the atomic oxygen produced by the torch. On the other hand, ozone and nitric oxide (NO) [ 39 ] formed through the reactions of O and O 2 and O and N, respectively, have a longer lifetime and can also be culprit.…”
Section: Plausible Mechanismmentioning
confidence: 99%
“…The cylindrical torch module, which uses the frame of a cylindrical tube having an outer diameter of 16.5 mm as the grounded outer electrode, is first described. This torch module is similar to that developed by Kuo et al [15][16][17], with the exceptions that the device is longer and has an integrated gas plenum chamber allowing for the module to be integrated into a supersonic combustor. Moreover, the central electrode has been replaced with a tungsten carbide tube providing an additional flow path for either air or fuel.…”
Section: Arc Torch Modulementioning
confidence: 99%
“…Consequently, the structures of these torches are relatively large and are therefore unsuitable for certain applications. The torch module patented by Kuo et al [15] can run in dc or low frequency ac mode and can produce low power (hundreds of watts) [16] or high power (a few kilowatts in 60 Hz periodic mode or hundreds of kilowatts in pulsed mode) [17] plasma torches. The size of the plasma torch produced by this module depends on the gas flow rate.…”
Section: Introductionmentioning
confidence: 99%